Airborne surveys of surface topographic condition over the coastal ice-free areas, continental ice sheet and sea-ice around the Lutzow-Holm Bay region, East Antarctica in 1996-1998 by JARE-38 - Masaki Kanao; Takashi Yamanouchi (Antarctic Record, 2000)
Preliminary airbone surveys for geoscientific and glaciological purposes were carried out by an aircraft (Cessna A185F) during the wintering season of the 38th Japanese Antarctic Research Expedition (JARE-38) in 1996-1998. First, several flights were conducted to investigate the relationship between snow-covered area and geological structure/topography on some outcrop surfaces along the Soya Coast and in the Prins Olav Coast region. Second, inland flights on the continental ice sheet were carried out to survey the surface conditions of bared blue ice and moraine areas on the Mizuho Plateau, about 50km eastward of the H-route. Then future prospects for geophysical and glaciological research were investigated. Moreover, feasibility surveys to determine the proper position of the airfield in the vicinity of Syowa Station were carried out in order to establish snow-ice runways for large aircraft for JARE in future. The recommended positions are located 1) near S16 and 2) eastward of the Langhovde region, where surface altitudes on the continental ice sheet are around 500m. In addition, surveys were carried out to detect changes of sea-ice distribution during the winter and to locate snow-vehicle routes in Lutzow-Holm Bay. Fifteen flights with a total of 43h55m flight hours were made for the present purpose in the whole season of JARE-38. Moreover, the surveys around the Amundsen Bay region were carried out using "Sikorsky S61A" helicopters of the icebreaker "Shirase" to decide future locations of seismic experiment lines for the "SEAL" project, along with the environmental assessments for the region.